Critical Thinking Implementation on EFL Students' Rhetorical Summary in Reading for Research Course - Putra, Ilham Devara Hendar (RETAIN, 2021)
In recent decades, the 21st-century skills alliance has established critical thinking skills to achieve students' success. The Rhetorical Summary was presented with the most efficient way to incorporate the students' critical thinking by constructing a highly organised summary to achieve this goal. Therefore, this study is conducted to present how EFL students' critical thinking is implemented in their rhetorical summary writing and investigate how they use their critical thinking in composing their rhetorical summary writing. English department students' rhetorical summary writing results would be the objects of this study. The subjects were 24 students in one of the Reading for Research Courses of State University of Surabaya. Next, to discuss the research objectives, three instruments were utilised in this study—two compulsory and one complementary. The first compulsory instrument is the rhetorical summary and critical thinking rubric, while the second one is the questionnaire. Additionally, the complementary instrument was an unstructured format interview guideline to strengthen the obtained data. It should be noted that the data would be analysed qualitatively through three stages: familiarising-organising, coding-reducing, and interpreting-representing. The results revealed that the students' critical thinking had been implemented in their rhetorical summary writing, particularly in each structure within the summary by following five critical thinking criteria: summarising topic or argument, considering previous assumptions, communicating a point of view, providing evidence of research, and drawing implications. Furthermore, it was discovered that the students used critical thinking to compose their rhetorical summary and determine their best solutions towards the challenges they encountered while writing is on the move.